Decline of Seriatopora (Scleractinia: Pocilloporidae) fecundity in Taiwan in 2018–2019. Issue 2 (7th February 2021) - Cirino, Luca; Tsai, Sujune; Kuo, Fu-Wen; Wen, Zhi-Hong; Meng, Pei-Jie; Lin, Chiahsin
ABSTRACT: Global warming and anthropogenic pressures present serious threats to coral reefs. Various stressors caused by human activities have been shown to negatively influence coral reproduction and recruitment. Because these threats are unlikely to abate in the immediate future, conservation projects involving larval release monitoring programmes are needed. Therefore, we measured larval release from captive colonies of a common Indo-Pacific reef coral, Seriatopora caliendrum, between October 2018 and December 2019. The largest larvae release event occurred in May 2019, and the smallest one occurred in September 2019. Several coral reproductive features demonstrated a close connection with seawater temperature. In contrast to prior studies conducted at the same institute with corals belonging to the same genus, of the same average size, originating from the same site, and cultured under the same conditions, we documented decreased fecundity of Seriatopora corals ex situ in 2018–2019. Various types of disturbance influence the study site from which corals were originally collected. We propose that local human activities and large-scale physical disturbances have negatively affected coral fecundity in southern Taiwan.